2014
DOI: 10.1039/c4ra05189k
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical study of the viability of conversion reactions as energy storage mechanisms

Abstract: Electroanalytical techniques indicate that voltage hysteresis in electrochemical conversion reactions has thermodynamic origins, which highlights the significant challenge to their prospects of application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Li + /Li. Thefirst conversion reactioninduces aconsistent structuralr earrangemento ft he electrode, [13] with formation of metallic Ni nanoclustersd ispersed in amorphous Li 2 Ot hat are convertedt on ano-aggregates of NiO upon subsequent charge. This may account for the consistent difference between the first discharge profile and the following ones, showings ignals of NiO conversion at about 1.4 vs. Li + /Li.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li + /Li. Thefirst conversion reactioninduces aconsistent structuralr earrangemento ft he electrode, [13] with formation of metallic Ni nanoclustersd ispersed in amorphous Li 2 Ot hat are convertedt on ano-aggregates of NiO upon subsequent charge. This may account for the consistent difference between the first discharge profile and the following ones, showings ignals of NiO conversion at about 1.4 vs. Li + /Li.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] When operating in al ithium cell, NiO is electrochemically reduced to metallic Ni nanoclusters dispersed in Li 2 Ou pon discharge andreconverted to NiO during the following charge, with concomitantm icrostructural rearrangement of the electrode. Studies on the reaction mechanism of NiO anodes [13,14] have highlighted the voltage hysteresis, first cycle inefficiency andp oor cycle life affecting the performances of this class of electrodes, still far from practical application. The optimization of the anode morphology is one of the strategies so far adopted in order to improve the NiO cyclability and efficiency.I th as been demonstrated that NiO with optimized morphology may achieve good performances both in terms of capacity retention and rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…This observation points to an analogy with conversion-type battery materials that display a similar initial flat plateau with low kinetic over-potential and for which the OCV also drifts for long periods (days to weeks) and departs substantially from the quasi-static potential traces at low currents or under PITT. 20,51,52 'Activation' in conversion materials is explained by an irreversible transformation of micro-sized starting particles into a nano-composite which interestingly afterwards cycles according to a rather sloped potential profile. 18,20 Conversion materials typically show stable voltage profiles once the 'micro to nano activation' is finished, in contrast with Li-rich materials which show continuous voltage fade with cycling.…”
Section: Discussionmentioning
confidence: 99%
“…20,51,52 'Activation' in conversion materials is explained by an irreversible transformation of micro-sized starting particles into a nano-composite which interestingly afterwards cycles according to a rather sloped potential profile. 18,20 Conversion materials typically show stable voltage profiles once the 'micro to nano activation' is finished, in contrast with Li-rich materials which show continuous voltage fade with cycling. The key difference in Li-rich materials is that their activation plateau is associated with anionic redox and in fact, such a plateau may be an early indication of structural instability of oxidized oxygen because it leads to reorganization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation